What eye-tracking tells us about reading-only and reading-while-listening in a first and second language. (July 2020) - Conklin, Kathy; Alotaibi, Sara; Pellicer-Sánchez, Ana; Vilkaitė-Lozdienė, Laura
Reading-while-listening has been shown to be advantageous in second language learning. However, research to date has not addressed how the addition of auditory input changes reading itself. Identifying how reading differs in reading-while-listening and reading-only might help explain the advantages associated with the former. The aim of the present study was to provide a detailed description of reading patterns with and without audio. To address this, we asked first language (L1) and second language (L2) speakers to read two passages (one in a reading-only mode and another in a reading-while-listening mode) while their eye movements were monitored. In reading-only, L2 readers had more and longer fixations (i.e. slower reading) than L1 readers. In reading-while-listening, eye-movement patterns were very similar in the L1 and L2. In general, neither group of participants fixated the word that they were hearing, although the L2 readers' eye movements were more aligned to the auditory input. When reading and listening were not aligned, both groups' eye movements generally preceded the audio. However, L2 readers had more cases where their fixations lagged behind the audio. We consider why reading slightly ahead of the audio could explain some of the benefits attributed to reading-while-listening contexts.